Natural disaster in Natal-RN: residents' perceptions (Research, Society and Development, 2021)
Natural disasters have been a global concern, considering that they can cause human and environmental material losses. They were responsible for 45% of all deaths in the last 50 years, due to climate change and extreme events. The city of Natal-RN has suffered from some risk events that leave the population vulnerable to natural hazards. Thus, this study deals with the natural disaster that happened in the neighborhood of Mãe Luiza in 2014, through reports from residents. The main objective is to analyze the residents' perception of the risk of natural disasters. To guide the reflections, this study mainly mobilizes themes related to natural disasters and perception in the light of phenomenology. The methodology is qualitative, exploratory and descriptive in nature, based on in-person interviews, taking the necessary precautions to carry out research with human beings, in accordance with the principles and procedures of the Comissão Nacional de Ética (CONEP) and the Comitê de Ética em Pesquisa (CEP). The results showed, based on the formulated questions, difficulties in understanding the risk of mass movement. It was found that some residents do not have a perception about the risk of disasters occurring. Therefore, it is essential to design sustainable awareness and training programs to ensure their success with the participation of the local population and, thus, implement natural disaster management based on the studied community.